2011
DOI: 10.1001/archpediatrics.2011.54
|View full text |Cite
|
Sign up to set email alerts
|

Unit-Based Care Teams and the Frequency and Quality of Physician-Nurse Communications

Abstract: To determine whether reorganizing physicians into unit-based teams in general pediatric wards is associated with greater ability to identify other care team members, increased face-to-face communication between physicians and nurses, greater perception that their patient care concerns were met, and decreased number of pages to residents. Design: Prospective intervention study with data collected before and at 2 time points after implementation of unit-based teams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…6,7 As such, the Accreditation Council of Graduate Medical Education emphasizes the quality of those hours, with a focus on several aspects of the resident working environment as key to improved educational and patient safety outcomes. [8][9][10] Geographic localization of physicians to patient care units has been proposed as a means to improve communication and agreement on plans of care, 11,12 and also to reduce resident workload by decreasing inefficiencies attributable to traveling throughout the hospital. 13 O'Leary, et al (2009) found that when physicians were localized to 1 hospital unit, there was greater agreement between physicians and nurses on various aspects of care, such as planned tests and anticipated length of stay.…”
Section: Resultsmentioning
confidence: 99%
“…6,7 As such, the Accreditation Council of Graduate Medical Education emphasizes the quality of those hours, with a focus on several aspects of the resident working environment as key to improved educational and patient safety outcomes. [8][9][10] Geographic localization of physicians to patient care units has been proposed as a means to improve communication and agreement on plans of care, 11,12 and also to reduce resident workload by decreasing inefficiencies attributable to traveling throughout the hospital. 13 O'Leary, et al (2009) found that when physicians were localized to 1 hospital unit, there was greater agreement between physicians and nurses on various aspects of care, such as planned tests and anticipated length of stay.…”
Section: Resultsmentioning
confidence: 99%
“…Effective interprofessional collaboration requires common shared perceptions and expectations of each team member’s role [11], [15], [19]: Collaboration between residents and nurses contributes to the quality of teamwork, a necessary condition for optimal patient care [2], [3], [4], [5], [6], [24]. Overall, the perceptions of residents and nurses in our study were similar to many items of the Jefferson Scale of Attitude toward Physician–Nurse Collaboration which are deemed important by a group of nursing students [25].…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized, controlled study, Curley [3] showed that interdisciplinary rounds in Internal Medicine decreased patients’ length of hospital stay and costs. Other studies showed that the same positive patient outcomes are associated with enhanced nurse-physician relationships [2], [4], [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…Five general characteristics of team effectiveness emerged from this study: understanding and respecting team members’ roles; recognizing that creating and maintaining teamwork is an ongoing process; sharing a common understanding of primary health care; having the practical “know-how” for sharing patient care; and communication [12]. Communication was identified as the essential factor in effective teams [9], [12], [13]: “Improving communication would increase understanding, co-operation, and collaboration among team members” [12]. In another focus-group study [14], clear goals and attention to teamwork were identified as factors needed for team effectiveness in primary care.…”
Section: Introductionmentioning
confidence: 93%
“…The hospital is a context of complex clinical practice, heavy workload, and numerous team shifts. The quality of interprofessional and multidisciplinary collaboration is crucial and has been shown to influence patients’ readmission to intensive care unit [6], patients’ length of stay [7], and other outcomes [8], [9], [10], [11]. Effective teamwork requires specific cognitive, technical, and affective competence, as determined in a focus-group study conducted in the field of primary care [12].…”
Section: Introductionmentioning
confidence: 99%